Factors affecting the registration of black South African civil engineering graduates with the Engineering Council of South Africa - Pillay, Manglin (My University, 2015)
ABSTRACT The objective of this research was to identify the factors affecting the professional registration of Black South African civil engineering graduates with the Engineering Council of South Africa. The main research question was, why, despite research hinting that the political and economic climate being in favour of the development of Black graduate civil engineering professionals, and that the processes for registration are clearly defined, only 12% of the registered engineering population are Black South Africans. What are the barriers that prevent civil engineering graduates from registering as professionals? The formulation of the research question was informed by the literature review. The research method adopted was a qualitative analysis. Data was collected by interviews with individual Black civil engineering graduates from various civil, construction and the built environment sectors. Central constructs were then identified and grouped together to formulate themes that eventually informed the outcomes of the research study. The research findings concluded that the factors which are barriers to professional registration for Black civil engineering graduates include weaknesses in the professional development programs and initiatives within organisations in both the private and public sectors. This included inefficient supervision, mentoring and coaching. The study also showed that the type and quality of work given to Black graduates is not suitable for the process of professional registration. Language was also found to be an inhibitor in social environments. Learning and knowledge transfer happening equally often in social events and corridor discussions as they do in formals project, business or mentoring meetings. The study concluded that the overall work experience and civil engineering culture in the work place, was incongruent with the aspirations of Black graduates. The experience was demotivating to the point that some graduates who shared a passion and purpose for civil engineering as a profession, now feel that they are possibly in the wrong career. There was also a clear indication that Black graduates need to become more acquainted with the professional registration processes and take charge of their career path in relation to the registration processes, and not rely on the system to direct their personal and professional development, and that the role of the bodies that govern civil engineering should become more prominent and attuned with the needs of the industry and its members. Various recommendations were presented to partners in the industry. The key recommendations includes the development of a macro, integrated and aligned process of professional registration that required practical and deliberate involvement of the individual, institutions, employers and the public sector with a view to achieve rapid transformation of the civil engineering sector, which is part of the national agenda of South Africa.
MBA 2015
Keywords: Civil engineers,Civil engineering -- Vocational guidance -- South Africa,College graduates, Black,Blacks -- Education (Higher